(untitled) (Sciences & Technologie. C, Biotechnologies, 2007)
The present study was designed to evaluate the oxidative stress-related parameters in streptozotocininduced diabetes in rats. After 2, 3, 6 and 12 weeks of hyperglycaemia the enzymatic parameters were measured in heart tissue of diabetic and control groups. Superoxide dismutase, glutathione peroxidase and the glucose-6-phosphate dehydrogenase activities significantly increased at all time intervals. Catalase activity increased initially (after 2 and 3 weeks), decreased after 6 weeks and increased again at the 12th week of the experiment. Glutathione reductase activity increased initially (at 2nd week), decreased below control level after 3 weeks, and then increased again. Ascorbic acid concentration decreased after 3 and 6 weeks, and increased at the 6th and 12th weeks. The level of lipid peroxidation products was reduced after 2, 3 and 6 weeks of the experiment. After 12 weeks it was significantly elevated. These data suggest that chronic hyperglycaemia induces oxidative stress in the heart but the defense mechanisms in the heart tissue are fairly efficacious against oxidative injury.